An Insight into 3Ps Coaches’ Knowledge and Its Integration to Coaching Practice and Sports Training Program: Filipino Context - Angoy, Raisalam Delos Trico; Ma'mun, H. Amung; Mahendra, Agus; Abduljabar, Bambang; Galendez, Jr., Procopio B (TEGAR: Journal of Teaching Physical Education in Elementary School, 2024)
In the sports landscape, coaching is undeniably considered important. However, coaching has focused mainly on competition, evaluating success through winning or performance excellence. In the case of Philippine sport, coaching largely remains entrenched in traditional performance-focused methods, where the primary goal of coaches is to enhance competitive outcomes. To date, there has been no research conducted in the Philippines focusing on sports coaching and training program with 3Ps integration. With this, the study aims to explore Filipino coaches' understanding of 3Ps and its incorporation into their coaching practices and training programs. Using the exploratory-descriptive qualitative research, nine Filipino coaches who are as well physical education teachers at higher education institutions in Mindanao, Philippines, participated in several in-depth interviews.  The study revealed six essential themes capturing the insights of Filipino coaches about 3Ps: unfamiliarity of 3Ps concept in coaching and training, lack of coaching practice and training standard, need of intentional teaching of 3Ps through coaching and training, recommendation of 3Ps for coaching development, support from government for coaching education, and 3Ps compliments existing coaching initiatives.  As this research contributes critical insights into the knowledge of Filipino coaches about 3Ps, thus, it is important in formulating conclusions and recommendations aimed at enhancing the sports coaching practice and training program in Philippines.